Studying light pollution as an emerging environmental concern in India - Komal Kaushik; Soumya Nair; Arif Ahamad (Journal of Urban Management, 2022)
The growing global population has increased the demands for urban housing development not only in the cities but in suburbs and rural areas as well. This gradual but speedy urbanization and globalization have introduced a new kind of "night lifestyle" among people, who engage in various entertainment activities late in the evening till early mornings. This influx of urban architecture and changes in lifestyles have resulted in increased use of various kinds of lighting systems in our cities to a point where some cities like Mumbai and New York City are known as "the cities that never sleep." Although this might be contributing significantly to the economy, they cause greater harm-light pollution, with little to no awareness. This paper, therefore, deals with the various types and causes, and thus the consequences of light pollution, ranging from plants, animals, humans to astronomy. The documentation done so far concerning light pollution has been done by scientists and astronomers from the West. Thus, an attempt has been made to assess the awareness ratio among Indians between the ages of 16-65 through an online questionnaire, analyzing the collected data qualitatively. It was found that majority of the participants were not aware about the term 'light pollution' and consequently were not aware about the threat that comes with it. So the objective of this review paper is to bring attention to the severity of the issue of light pollution and make people aware of the consequences it has on our lives. All the effective mitigation policies and regulations from various countries around the world that were theorized to deal with this risk and propagate awareness are included. Our goal is to bring these solutions to practice in the Asian and South Asian countries like India and make the masses informed as light pollution is still a relatively new and alien concept.
Keywords: 710; Artificial light; India and Awareness; Light pollution; Night sky; Questionnaire survey; Urbanization